POLIMEROSSOMOS VERSUS LIPOSSOMOS: A EVOLUÇÃO DA “BALA MÁGICA” - Apolinário,Alexsandra Conceição (2017)
Polymeric vesicles known as polymersomes are formed by the self-assemble of amphiphilic block copolymers and have structural organization similar to liposomes. However, polymersomes present higher physicochemical stability and structure versatility due to their polymeric nature. In this review we describe the main aspects related to the structure and applications of these systems for drug delivery.